PENGARUH MEDIA TANAM DAN PEMUPUKAN UREA TERHADAP PERTUMBUHAN DAN PRODUKSI SAWI (Brassica juncea L.) - Pudyartono, - (saintis, 2009)
Vegetable greens are consumed, either after being processed as well as fresh vegetables, it contains various essential nutrients for health, besides having the content of vitamins or nutrients essential for health, mustard greens can be in believing to eliminate throat itching in patients with cough. It can also be a healer for headaches and may improve kidney function. This research has purpose to know the effect of growing media and fertilizers Urea (N) on the growth and production of Indian mustard (Brassica juncea L.). Materials used in this research that green cabbage F1 hybrid seed, fertilizer, urea, NPK fertilizer, cow manure, compost, sand, soil, polybags, Furadan 3G. Conclusions of research are an interaction on all parameters including the observation of growth and production of mustard. The best treatment combination in the treatment of planting media soil types: cow manure: compost (1: 1: 1) by urea fertilization 200 kg / ha (M2 U2)